Consolidation of construction material by biomineralization process - García, Pilar (2018)
In this study the work of induction of microbial carbonate genesis was carried out in order to obtain an improvement in the consolidation of the materials used in construction such as mortars and paving stones, in order to confer them greater resistance and conservation. As a result of the tests carried out, it was found that the inclusion of a bacterial biomass culture formed by bacteria of the genus Bacillus sp., in the formulation of the mortar and paving stones, helped to increase the resistance to compression with Fc values. 266.3 kg/cm2 higher compared to the control of Fc 261.0 kg/cm2. Also, the state of aggregation of the particles improved remarkably, we observed that in the fragmentation tests the structures showed a geometrically more homogeneous grid, compared with the cobbles of the control test. Regarding the texture and roughness aspects, it was proved that the paving stones cured with bacterial cultures remarkably improved these characteristics, besides evidencing a more whitish coloration, with pores with light and homogeneous colored particles, of better appearance than the control. However, in the tests carried out by changing the formulation of the preparation of mortars and pavers with the inclusion of rice husk, the results of curing with bacteria did not show any improvement in the consolidation process by means of carbonategenesis.